The rising trend of coagulase-negative staphylococci in neonatal septicemia - Vijaya Shivanna; S R Sunkappa; D Venkatesha (Wolters Kluwer Medknow Publications, 2016)
Neonatal septicemia is one of the leading causes of neonatal mortality and morbidity worldwide. Hence, the present study was undertaken to isolate the bacteria causing neonatal sepsis and determine their antibiotic susceptibility pattern. Fifty neonates suspected to have septicemia were screened for 2 months (July and August 2014). Out of 50 specimen, 15 (30%) were blood culture positive. Coagulase-negative staphylococci was the most common isolate (10, 66.6%), with 60% (6 isolates) methicillin resistance. In view of the increasing antibiotic resistance, periodic surveillance should be conducted to control the emergence and spread of antimicrobial resistance.